Critique, risqué: A comment on Didier Fassin - Holbraad, Martin (Anthropological theory, 2017)
In response to Didier Fassin’s penetrating argument about the enduring role of critique in anthropology, the present comment suggests that the most powerful critical moment for anthropology may derive from its encounter with ethnographical materials that have the power reflexively to reconfigure its analytical infrastructure. But if this is the case, then critique itself, as a part of anthropology’s analytical infrastructure, must also be subject to the same critical operation, open to experimental redefinition as and when its encounters with ethnography make a difference to it. In the current atmosphere of ‘post-truth’, this might be one of the most politically consequent risks anthropology needs to take with itself.